KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA SEKTOR PERBANKAN (Studi Kasus Pada Pelanggan PT Bank Artha Graha Internasional, Tbk) - Estiana, Ria; Susanti, Ari (JAB (Jurnal Akuntansi & Bisnis), 2017)
This study aims to determine the factors that influence customer satisfaction, the most important criteria that can affect customer satisfaction and analyze the level of customer satisfaction in Banking. This research was conducted at PT. Bank Artha Graha International, Tbk and is a quantitative descriptive study with a case study approach. The sample in this study is the customers of PT. Bank Artha Graha International, Tbk, and this research data in the form of primary data sourced from the questionnaire.The results of this study indicate that customer satisfaction about the quality of service at Bank Artha Graha is quite high at 62.05%.Â Keywords: service quality, customer satisfaction